Skip to main content

On two kinds of the reverse half-discrete Mulholland-type inequalities involving higher-order derivative function

Abstract

By means of the weight functions, Hermite–Hadamard’s inequality, and the techniques of real analysis, a new more accurate reverse half-discrete Mulholland-type inequality involving one higher-order derivative function is given. The equivalent statements of the best possible constant factor related to a few parameters, the equivalent forms, and several particular inequalities are provided. Another kind of the reverses is also considered.

Introduction

Suppose that \(p > 1\), \(\frac{1}{p} + \frac{1}{q} = 1\), \(a_{m},b_{n} \ge 0\), \(0 < \sum_{m = 1}^{\infty } a_{m}^{p} < \infty \), and \(0 < \sum_{n = 1}^{\infty } b_{n}^{q} < \infty \). We have the following Hardy–Hilbert’s inequality with the best possible constant factor \(\frac{\pi }{\sin (\pi /p)}\) (cf. [1], Theorem 315):

$$ \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{1}{m + n} a_{m}b_{n} < \frac{\pi }{\sin (\pi /p)} \Biggl(\sum_{m = 1}^{\infty } a_{m}^{p} \Biggr)^{\frac{1}{p}} \Biggl(\sum _{n = 1}^{\infty } b_{n}^{q} \Biggr)^{\frac{1}{q}}. $$
(1)

Replacing \(\frac{1}{m + n}\) with \(\frac{1}{m + n - 1}\) in (1), we have a more accurate form of (1) (cf. [1], Theorem 323). We still have the following Mulholland’s inequality with the same best possible constant factor of (1) (cf. [1], Theorem 343):

$$ \sum_{m = 2}^{\infty } \sum _{n = 2}^{\infty } \frac{1}{\ln mn} a_{m}b_{n} < \frac{\pi }{\sin (\pi /p)} \Biggl(\sum_{m = 2}^{\infty } m^{p - 1}a_{m}^{p} \Biggr)^{\frac{1}{p}} \Biggl(\sum _{n = 2}^{\infty } n^{q - 1}b_{n}^{q} \Biggr)^{\frac{1}{q}}. $$
(2)

In 2006, by means of Euler–Maclaurin’s summation formula, Krnic et al. [2] provided an extension of (1) as follows:

$$ \sum_{m = 1}^{\infty } \sum _{n = 1}^{\infty } \frac{a_{m}b_{n}}{(m + n)^{\lambda }} < B(\lambda _{1},\lambda _{2}) \Biggl[\sum _{m = 1}^{\infty } m^{p(1 - \lambda _{1}) - 1}a_{m}^{p} \Biggr]^{\frac{1}{p}} \Biggl[\sum_{n = 1}^{\infty } n^{q(1 - \lambda _{2}) - 1}b_{n}^{q} \Biggr]^{\frac{1}{q}}, $$
(3)

where \(\lambda _{i} \in (0,2]\) (\(i = 1,2\)), \(\lambda _{1} + \lambda _{2} = \lambda \in (0,4]\), and the constant factor \(B(\lambda _{1},\lambda _{2})\) is best possible, \(B(u,v) = \int _{0}^{\infty } \frac{t^{u - 1}}{(1 + t)^{u + v}}\,dt\) (\(u,v > 0\)) is the beta function. For \(p = q = 2\), \(\lambda _{1} = \lambda _{2} = \frac{\lambda }{2}\), inequality (3) reduces to the published result in [3].

In 2019, by using (2) and Abel’s summation by parts formula, Adiyasuren et al. [4] published a Hardy–Hilbert-type inequality with the kernel as \(\frac{1}{(m + n)^{\lambda }}\) involving partial sums. Inequalities (1)–(3) with their reverses play an important role in analysis and its applications (cf. [515]).

In 1934, Hardy et al. [1] also published a half-discrete Hilbert-type inequality in Theorem 351: If \(K(t)\) (\(t > 0\)) is decreasing, \(p > 1\), \(\frac{1}{p} + \frac{1}{q} = 1\), \(0 < \phi (s) = \int _{0}^{\infty } K(t)t^{s - 1}\,dt < \infty \), \(a_{n} \ge 0\), such that \(0 < \sum_{n = 1}^{\infty } a_{n}^{p} < \infty \), then

$$ \int _{0}^{\infty } x^{p - 2} \Biggl(\sum _{n = 1}^{\infty } K(nx)a_{n} \Biggr)^{p}\,dx < \phi ^{p} \biggl(\frac{1}{q} \biggr) \sum_{n = 1}^{\infty } a_{n}^{p}. $$
(4)

Some new extensions of (4) were given in [1620].

In 2016, by the use of the techniques of real analysis, Hong et al. [21] gave an equivalent statement of the best possible constant factor related to several parameters in the general form of (1). The other similar results were provided by [2229]. Recently, Yang et al. [30] gave a new result in a reverse half-discrete Hilbert-type inequality.

In this paper, following the way of [4, 21], by means of the weight functions, Hermite–Hadamard’s inequality, and the techniques of real analysis, a new more accurate reverse half-discrete Mulholland-type inequality with the kernel as \(\frac{1}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\) involving one higher-order derivative function is given. The equivalent statements of the best possible constant factor related to a few parameters, the equivalent forms, and several particular inequalities are provided. Another kind of the reverses is also considered.

Some lemmas

In what follows, we suppose that \(p < 1\) (\(p \ne 0\)), \(\frac{1}{p} + \frac{1}{q} = 1\), \(\mathrm{N}: = \{ 1,2, \ldots \}\), \(\mathrm{m} \in \mathrm{N} \cup \{ 0\}\), \(\alpha \in (0,1]\), \(\xi \in [0, \frac{1}{2} ]\), \(\lambda \in (0,\infty )\), \(\lambda _{1} \in (0,\lambda )\), \(\lambda _{2} \in (0,\lambda ) \cap (0,\frac{1}{\alpha } ]\),

$$\begin{aligned}& k_{\lambda } (\lambda _{i}): = B(\lambda _{i},\lambda - \lambda _{i})\quad (i = 1,2), \end{aligned}$$

\(\hat{\lambda }_{1}: = \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\), \(\hat{\lambda }_{2}: = \frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p}\). We also assume that \(f(x) = f^{(0)}(x)\) is a continuous derivative function of m-order unless finite points in \(R_{ +}: = (0,\infty )\), \(f^{(k - 1)}(y) \ge 0\), \(f^{(k - 1)}(0 + ) = 0\), \(f^{(k - 1)}(x) = o(e{}^{tx})\) (\(t > 0\); \(x \to \infty \)) (\(k = 1, \ldots ,m\)), and for \(f^{(m)}(x)\), \(a_{n} \ge 0\), \(0 < \int _{0}^{\infty } x^{p(1 - \hat{\lambda }_{1}) - 1} (f^{(m)}(x))^{p}\,dx < \infty \), and

$$ 0 < \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \hat{\lambda }_{2}) - 1}( n - \xi )^{q - 1}a_{n}^{q} < \infty . $$

Lemma 1

Define the following weight function:

$$ \varpi _{\lambda } (\lambda _{2},x): = \alpha x^{\lambda - \lambda _{2}}\sum _{n = 2}^{\infty } \frac{[\ln (n - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda } (n - \xi )}\quad (x \in \mathrm{R}_{ +} ). $$
(5)

We have the following inequalities:

$$ 0 < k_{\lambda } (\lambda _{2}) \biggl[1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr] < \varpi _{\lambda } (\lambda _{2},x) < k_{\lambda } (\lambda _{2})\quad (x \in \mathrm{R}_{ +} ), $$
(6)

where we define \(O(\frac{1}{x^{\lambda _{2}}}): = \frac{1}{k_{\lambda } (\lambda _{2})}\int _{0}^{\frac{\ln ^{\alpha } (2 - \xi )}{x}} \frac{v^{\lambda _{2} - 1}}{(1 + v)^{\lambda }}\,dv\) satisfying \(0 < O(\frac{1}{x^{\lambda _{2}}}) < \frac{\ln ^{\alpha \lambda _{2}}(2 - \xi )}{k_{\lambda } (\lambda _{2})x^{\lambda _{2}}}\).

Proof

For fixed \(x \in \mathrm{R}_{ +}\), the function \(g(t): = \frac{[\ln (t - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )}\) is strictly decreasing and strictly convex in \((\frac{3}{2},\infty )\). In fact, for \(\alpha \in (0,1]\), \(\lambda _{2} \in (0,\frac{1}{\alpha } ]\), \(\xi \in [0,\frac{1}{2}]\), \(t \in (\frac{3}{2},\infty )\),

$$\begin{aligned}& \frac{d}{d\mathrm{t}}g(t) = - \frac{(1 - \alpha \lambda _{2})[\ln (t - \xi )]^{\alpha \lambda _{2} - 2}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )^{2}} - \frac{\lambda \alpha [\ln (t - \xi )]^{\alpha \lambda _{2} + \alpha - 2}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda + 1}(t - \xi )^{2}} \\& \hphantom{\frac{d}{d\mathrm{t}}g(t) =}{} - \frac{[\ln (t - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )^{2}} < 0, \\& \frac{d^{2}}{d\mathrm{t}^{2}}g(t) = \frac{(1 - \alpha \lambda _{2})(2 - \alpha \lambda _{2})[\ln (t - \xi )]^{\alpha \lambda _{2} - 3}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )^{3}} + \frac{\lambda \alpha (3 - 2\alpha \lambda _{2} - \alpha )[\ln (t - \xi )]^{\alpha \lambda _{2} + \alpha - 3}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda + 1}(t - \xi )^{3}} \\& \hphantom{\frac{d^{2}}{d\mathrm{t}^{2}}g(t) =}{}+ \frac{3(1 - \alpha \lambda _{2})[\ln (t - \xi )]^{\alpha \lambda _{2} - 2}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )^{3}} + \frac{\lambda \alpha ^{2}(\lambda + 1)[\ln (t - \xi )]^{\alpha \lambda _{2} + 2\alpha - 3}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda + 2}(t - \xi )^{3}} \\& \hphantom{\frac{d^{2}}{d\mathrm{t}^{2}}g(t) =}{}+ \frac{3\lambda \alpha [\ln (t - \xi )]^{\alpha \lambda _{2} + \alpha - 2}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda + 1}(t - \xi )^{3}} + \frac{2[\ln (t - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )^{3}} > 0. \end{aligned}$$

By the decreasingness property of series and Hermite–Hadamard’s inequality (cf. [31]), we have

$$\begin{aligned} \int _{2}^{\infty } \frac{[\ln (t - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )}\,dt < & \sum _{n = 2}^{\infty } \frac{[\ln (n - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda } (n - \xi )} \\ < & \int _{\frac{3}{2}}^{\infty } \frac{[\ln (t - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )}\,dt. \end{aligned}$$
(7)

Setting \(v = \frac{\ln ^{\alpha } (t - \xi )}{x}(\frac{1}{t - \xi }\,dt = \frac{1}{\alpha } x^{\frac{1}{\alpha }} v^{\frac{1}{\alpha } - 1}\,dv)\), for \(\frac{3}{2} - \xi \ge 1\), we obtain

$$\begin{aligned}& \int _{\frac{3}{2}}^{\infty } \frac{[\ln (t - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )}\,dt \\& \quad = \frac{1}{\alpha x^{\lambda }} \int _{\frac{\ln ^{\alpha } (\frac{3}{2} - \xi )}{x}}^{\infty } \frac{(xv)^{{\frac{1}{\alpha } (\alpha \lambda _{2} - 1)}}}{(1 + v)^{\lambda }} x^{\frac{1}{\alpha }} v^{\frac{1}{\alpha } - 1}\,dv \le \frac{1}{\alpha x^{\lambda - \lambda _{2}}} \int _{0}^{\infty } \frac{v^{\lambda _{2} - 1}\,dv}{(1 + v)^{\lambda }} = \frac{1}{\alpha x^{\lambda - \lambda _{2}}}k_{\lambda } (\lambda _{2}). \end{aligned}$$

By (5) and (7), we have

$$ \varpi _{\lambda } (\lambda _{2},x) < \alpha x^{\lambda - \lambda _{2}} \frac{1}{\alpha x^{\lambda - \lambda _{2}}}k{}_{\lambda } (\lambda _{2}) = k{}_{\lambda } (\lambda _{2}). $$

On the other hand, in the same way, we find

$$\begin{aligned} \varpi _{\lambda } (\lambda _{2},x) >& \alpha x^{\lambda - \lambda _{2}} \int _{2}^{\infty } \frac{[\ln (t - \xi )]^{\alpha \lambda _{2} - 1}}{[x + \ln ^{\alpha } (t - \xi )]^{\lambda } (t - \xi )}\,dt \\ =& \int _{0}^{\infty } \frac{v^{\lambda _{2} - 1}\,dv}{(1 + v)^{\lambda }} - \int _{0}^{\frac{\ln ^{\alpha } (2 - \xi )}{x}} \frac{v^{\lambda _{2} - 1}\,dv}{(1 + v)^{\lambda }} = k_{\lambda } (\lambda _{2}) \biggl[1 - O \biggl(\frac{1}{x^{\lambda _{2}}} \biggr) \biggr], \end{aligned}$$

where \(O(\frac{1}{x^{\lambda _{2}}}) = \frac{1}{k_{\lambda } (\lambda _{2})}\int _{0}^{\frac{\ln ^{\alpha } (2 - \xi )}{x}} \frac{v^{\lambda _{2} - 1}}{(1 + v)^{\lambda }}\,dv\) satisfying

$$ 0 < O \biggl(\frac{1}{x^{\lambda _{2}}} \biggr) < \frac{1}{k_{\lambda } (\lambda _{2})} \int _{0}^{\frac{\ln ^{\alpha } (2 - \xi )}{x}} v^{\lambda _{2} - 1}\,dv = \frac{\ln ^{\alpha \lambda _{2}}(2 - \xi )}{k_{\lambda } (\lambda _{2})x^{\lambda _{2}}}\quad (x > 0). $$

Hence, inequalities (6) follow.

The lemma is proved. □

Lemma 2

For \(p < 0\) (\(0 < q < 1\)), we have the following reverse Mulholland-type inequality:

$$\begin{aligned} I_{0} : =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda }} f^{(m)}(x)\,dx > \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \\ &{}\times \biggl[ \int _{0}^{\infty } x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \hat{\lambda }_{2}) - 1}(n - \xi )^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(8)

Proof

For \(\alpha > 0\), setting \(v = x/\ln ^{\alpha } (n - \xi )\), we can obtain another weight function:

$$\begin{aligned} \omega _{\lambda } (\lambda _{1},n) : =& \bigl[\ln (n - \xi ) \bigr]^{\alpha (\lambda - \lambda _{1})} \int _{0}^{\infty } \frac{x^{\lambda _{1} - 1}\,dx}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda }} \\ =& \int _{0}^{\infty } \frac{v^{\lambda _{1} - 1}\,dv}{(v + 1)^{\lambda }} = k_{\lambda } (\lambda _{1})\quad \bigl(n \in \mathrm{N}\backslash \{ 1\} \bigr). \end{aligned}$$
(9)

By reverse Hölder’s inequality (cf. [31]), we have

$$\begin{aligned} I_{0} =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{1}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda }} \biggl\{ \frac{x^{(1 - \lambda {}_{1})/q}(n - \xi )^{ - 1/p}}{[\ln (n - \xi )]^{(1 - \alpha \lambda _{2})/p}}f^{(m)}(x) \biggr\} \biggl\{ \frac{[\ln (n - \xi )]^{(1 - \alpha \lambda _{2})/p}}{x^{(1 - \lambda {}_{1})/q}(n - \xi )^{ - 1/p}}a_{n} \biggr\} \,dx \\ \ge& \Biggl\{ \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{1}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda }} \frac{x^{(1 - \lambda {}_{1})(p - 1)}(n - \xi )^{ - 1}}{[\ln (n - \xi )]^{1 - \alpha \lambda _{2}}} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \Biggr\} ^{\frac{1}{p}} \\ &{} \times \Biggl\{ \sum_{n = 2}^{\infty } \int _{0}^{\infty } \frac{1}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda }} \frac{[\ln (n - \xi )]^{(1 - \alpha \lambda _{2})(q - 1)}a_{n}^{q}}{x^{1 - \lambda {}_{1}}(n - \xi )^{1 - q}} \,dx \Biggr\} ^{\frac{1}{q}} \\ =& \biggl\{ \frac{1}{\alpha } \int _{0}^{\infty } \varpi _{\lambda } (\lambda _{2},x) x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p} \,dx \biggr\} ^{\frac{1}{p}} \\ &{}\times \Biggl\{ \sum_{n = 2}^{\infty } \omega _{\lambda } (\lambda {}_{1},n) \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \hat{\lambda }_{2}) - 1}(n - \xi )^{q - 1}a_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(10)

We show that (10) does not keep the form of equality. Otherwise (cf. [31]), there exist constants A and B such that both of them are not zero and

$$ A\frac{x^{(1 - \lambda {}_{1})(p - 1)}(n - \xi )^{ - 1}}{[\ln (n - \xi )]^{1 - \alpha \lambda _{2}}} \bigl(f^{(m)}(x) \bigr)^{p} = B \frac{[\ln (n - \xi )]^{(1 - \alpha \lambda _{2})(q - 1)}a_{n}^{q}}{x^{1 - \lambda {}_{1}}(n - \xi )^{1 - q}}\quad \text{a.e. in }\mathrm{R}_{ +} \times \mathrm{N} \backslash \{ 1\}. $$

Assuming that \(A \ne 0\), there exists \(n \in \mathrm{N}\backslash \{ 1\} \) satisfying

$$ x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p} = \frac{B}{A} \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2})}(n - \xi )^{ - q}a_{n}^{q}\frac{1}{x^{1 + (\lambda - \lambda _{1} - \lambda _{2})}}\quad \text{a.e. in }\mathrm{R}_{ +}, $$

which contradicts the fact that \(0 < \int _{0}^{\infty } x^{p(1 - \hat{\lambda }_{1}) - 1} (f^{(m)}(x))^{p}\,dx < \infty \), since \(\int _{0}^{\infty } \frac{1}{x^{1 + (\lambda - \lambda _{1} - \lambda _{2})}}\,dx = \infty \). Then, by (6) and (9), we have (8).

The lemma is proved. □

Lemma 3

For \(t > 0\), we have the following expression:

$$ \int _{0}^{\infty } e^{ - tx} f(x)\,dx = \frac{1}{t^{m}} \int _{0}^{\infty } e^{ - tx} f^{(m)}(x) \,dx. $$
(11)

Proof

For \(m = 0\), in view of \(f^{(0)}(x) = f(x)\), (11) is valid. For \(m \in \mathrm{N}\), since \(f^{(k - 1)}(0 + ) = 0\) (\(k = 1, \ldots ,m\)), integration by parts, we find

$$\begin{aligned} \int _{0}^{\infty } e^{ - tx} f^{(k)}(x) \,dx =& \int _{0}^{\infty } e^{ - tx}\,df^{(k - 1)}(x) \\ =& e^{ - tx}f^{(k - 1)}(x)|_{0}^{\infty } - \int _{0}^{\infty } f^{(k - 1)} (x) \,de^{ - tx} \\ =& \lim_{x \to \infty } \frac{f^{(k - 1)}(x)}{e^{tx}} + t \int _{0}^{\infty } e^{ - tx} f^{(k - 1)}(x) \,dx. \end{aligned}$$

In view of

$$ f^{(k - 1)}(x) = o \bigl(e{}^{tx} \bigr)\quad (t > 0,x \to \infty ;k = 1, \ldots ,m), $$

it follows that \(\lim_{x \to \infty } \frac{f^{(k - 1)}(x)}{e^{tx}} = 0\), and then

$$ \int _{0}^{\infty } e^{ - tx} f^{(k - 1)}(x) \,dx = \frac{1}{t} \int _{0}^{\infty } e^{ - tx} f^{(k)}(x) \,dx. $$

By substitution of \(k = 1, \ldots ,m\) in the above expression, (11) follows.

The lemma is proved. □

Main results

Theorem 1

For \(p < 0\) (\(0 < q < 1\)), we have the following more accurate reverse half-discrete Mulholland-type inequality involving one higher-order derivative function:

$$\begin{aligned} I : =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}} f(x)\,dx > \frac{\Gamma (\lambda )}{\Gamma (\lambda + m)} \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \\ &{}\times \biggl[ \int _{0}^{\infty } x^{p(1 - \stackrel{\leftarrow }{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \stackrel{\leftarrow }{\lambda }_{2}) - 1}(n - \xi )^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(12)

In particular, for \(\lambda _{1} + \lambda _{2} = \lambda \), we have

$$ 0 < \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx < \infty ,\qquad 0 < \sum _{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2}) - 1} (n - \xi )^{q - 1}a_{n}^{q} < \infty , $$

and the following inequality:

$$\begin{aligned} I =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}} f(x)\,dx \\ >&\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}) \\ &{}\times \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)} (x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2}) - 1}(n - \xi ){}^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(13)

Proof

Since we have

$$ \frac{1}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}} = \frac{1}{\Gamma (\lambda + m)} \int _{0}^{\infty } t^{\lambda + m - 1} e^{ - [x + \ln ^{\alpha } (n - \xi )]t} \,dt, $$

by the Lebesgue term by term integration theorem (cf. [32]) and (11), we find

$$\begin{aligned} I =& \frac{1}{\Gamma (\lambda + m)} \int _{0}^{\infty } \sum_{n = 2}^{\infty } a_{n}f(x) \int _{0}^{\infty } t^{\lambda + m - 1} e^{ - [x + \ln ^{\alpha } (n - \xi )]t}\,dt \,dx \\ =& \frac{1}{\Gamma (\lambda + m)} \int _{0}^{\infty } t^{\lambda + m - 1} \biggl( \int _{0}^{\infty } e^{ - xt}f(x)\,dx \biggr)\sum _{n = 2}^{\infty } e^{ - t\ln ^{\alpha } (n - \xi )}a_{n} \,dt \\ =& \frac{1}{\Gamma (\lambda + m)} \int _{0}^{\infty } t^{\lambda + m - 1} \biggl(t^{ - m} \int _{0}^{\infty } e^{ - xt}f^{(m)}(x) \,dx \biggr)\sum_{n = 2}^{\infty } e^{ - t\ln ^{\alpha } (n - \xi )}a_{n}\,dt \\ =& \frac{1}{\Gamma (\lambda + m)} \int _{0}^{\infty } \sum_{n = 2}^{\infty } a_{n}f^{(m)}(x) \biggl\{ \int _{0}^{\infty } t^{\lambda - 1} e^{ - [x + \ln ^{\alpha } (n - \xi )]t}\,dt \biggr\} \,dx \\ =& \frac{\Gamma (\lambda )}{\Gamma (\lambda + m)} \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda }} f^{(m)}(x)\,dx = \frac{\Gamma (\lambda )}{\Gamma (\lambda + m)}I_{0}. \end{aligned}$$

Then, by (8), we have (12).

The theorem is proved. □

Theorem 2

For \(p < 0\) (\(0 < q < 1\)), if \(\lambda _{1} + \lambda _{2} = \lambda \), then the constant factor

$$ \frac{\Gamma (\lambda )}{\Gamma (\lambda + m)} \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} $$

in (12) is best possible. On the other hand, if we add the condition that \(\lambda - \lambda _{1} \le \frac{1}{\alpha }\), the same constant factor in (12) is best possible, then \(\lambda _{1} + \lambda _{2} = \lambda \).

Proof

In the following, for \(m = 0\), \(\varepsilon \ge 0\), we define \(\prod_{i = 0}^{m - 1} (\lambda _{1} + i - \frac{\varepsilon }{p} ) = 1\).

\(If\lambda _{1} + \lambda _{2} = \lambda \), then (12) reduces to (13). For any \(0 < \varepsilon < q\lambda _{2}\), we set

$$\begin{aligned}& \tilde{f}^{(0)}(x) = \tilde{f}(x): = \textstyle\begin{cases} 0,&0 < x < 1, \\ x^{\lambda _{1} + m - \frac{\varepsilon }{p} - 1},&x \ge 1 \end{cases}\displaystyle , \\& \tilde{a}_{n}: = \bigl[\ln (n - \xi ) \bigr]^{\alpha (\lambda _{2} - \frac{\varepsilon }{q}) - 1}(n - \xi )^{ - 1}\quad \bigl(n \in \mathrm{N}\backslash \{ 1\} \bigr), . \end{aligned}$$

and find

$$ \tilde{f}^{(k)}(x) = \textstyle\begin{cases} 0,\quad 0 < x < 1, \\ \prod_{i = 0}^{k - 1} (\lambda _{1} + i - \frac{\varepsilon }{p})x^{\lambda _{1} + m - k - \frac{\varepsilon }{p} - 1},\quad x > 1 \end{cases}\displaystyle (k = 0, \ldots ,m) $$

satisfying \(\tilde{f}^{(k)}(0 + ) = 0\), \(\tilde{f}^{(k)}(x) = o(e{}^{tx})\) (\(t > 0\), \(x \to \infty \); \(k = 0, \ldots ,m - 1\)).

If there exists a constant \(M( \ge \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}))\) such that (13) is valid when we replace \(\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2})\) with M, then in particular we have

$$\begin{aligned} \tilde{I} : =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{\tilde{a}_{n}\tilde{f}(x)}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \\ >& M \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl( \tilde{f}^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2}) - 1}(n - \xi )^{q - 1} \tilde{a}_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(14)

By the decreasingness property of series, we find

$$\begin{aligned} \tilde{I} >& M\prod_{i = 0}^{m - 1} \biggl( \lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl[ \int _{1}^{\infty } x^{p(1 - \lambda _{1}) - 1} x^{p(\lambda _{1} - 1) - \varepsilon } \,dx \biggr]^{\frac{1}{p}} \\ &{}\times \Biggl\{ \sum_{n = 2}^{\infty } \bigl[ \ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2}) - 1}(n - \xi )^{q - 1} \bigl[\ln (n - \xi ) \bigr]^{q\alpha \lambda _{2} - \alpha \varepsilon - q}(n - \xi )^{ - q} \Biggr\} ^{\frac{1}{q}} \\ =& M\prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl( \int _{1}^{\infty } x^{ - \varepsilon - 1}\,dx \biggr)^{\frac{1}{p}} \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(n - \xi )^{ - 1} \Biggr\} ^{\frac{1}{q}} \\ >& M\prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl( \int _{1}^{\infty } x^{ - \varepsilon - 1}\,dx \biggr)^{\frac{1}{p}} \biggl\{ \int _{2}^{\infty } \bigl[\ln (y - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(y - \xi )^{ - 1}\,dy \biggr\} ^{\frac{1}{q}} \\ =& \frac{M}{\varepsilon } \prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl\{ \frac{1}{\alpha } \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon } \biggr\} ^{\frac{1}{q}}. \end{aligned}$$

Replacing λ with \(\lambda + m\), setting \(\tilde{\lambda }_{2}: = \lambda _{2} - \frac{\varepsilon }{q} \in (0,\lambda + m) \cap (0,\frac{1}{\alpha } ]\), \(\tilde{\lambda }_{1}: = \lambda _{1} + m + \frac{\varepsilon }{q} \in (0,\lambda + m)\) in (5), by (6), we have

$$\begin{aligned} \tilde{I} =& \int _{1}^{\infty } \Biggl\{ x^{\lambda _{1} + m + \frac{\varepsilon }{q}} \sum _{n = 2}^{\infty } \frac{[\ln (n - \xi )]^{\alpha (\lambda _{2} - \frac{\varepsilon }{q}) - 1}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}(n - \xi )} \Biggr\} x^{ - \varepsilon - 1}\,dx \\ =& \frac{1}{\alpha } \int _{1}^{\infty } \varpi _{\lambda + m}(\tilde{\lambda }_{2},x) x^{ - \varepsilon - 1}\,dx \\ < & \frac{1}{\alpha } \int _{1}^{\infty } k_{\lambda + m}(\tilde{\lambda }_{2}) x^{ - \varepsilon - 1}\,dx = \frac{1}{\varepsilon \alpha } k_{\lambda + m}( \tilde{\lambda }_{2}). \end{aligned}$$

Based on the above results, we have

$$ \frac{1}{\alpha } k_{\lambda + m}(\tilde{\lambda }_{2}) > \varepsilon \tilde{I} > M\prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl\{ \frac{1}{\alpha } \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon } \biggr\} ^{\frac{1}{q}}. $$

For \(\varepsilon \to 0^{ +} \), in view of the continuity of the beta function, it follows that

$$ \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda {}_{1},\lambda _{2}) = \frac{\Gamma (\lambda {}_{1})\Gamma (\lambda {}_{2})}{\alpha ^{1/p}\Gamma (\lambda + m)} = \frac{B(\lambda _{1} + m,\lambda _{2})}{\alpha ^{1/p}\prod_{i = 0}^{m - 1} (\lambda _{1} + i)} \ge M. $$

Hence, \(M = \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2})\) is the best possible constant factor in (13).

On the other hand, for \(\hat{\lambda }_{1} = \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q}\), \(\hat{\lambda }_{2} = \frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p}\), \(\lambda - \lambda _{1} \le \frac{1}{\alpha }\), we find

$$\begin{aligned}& \hat{\lambda }_{1} + \hat{\lambda }_{2} = \frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q} + \frac{\lambda - \lambda _{1}}{q} + \frac{\lambda _{2}}{p} = \lambda , \\& 0 < \hat{\lambda }_{1},\qquad \hat{\lambda }_{2} < \frac{\lambda }{p} + \frac{\lambda }{q} = \lambda ,\qquad \hat{\lambda }_{2} \le \frac{1/\alpha }{p} + \frac{1/\alpha }{q} = \frac{1}{\alpha }, \end{aligned}$$

and \(\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\hat{\lambda }_{1},\hat{\lambda }_{2}) \in \mathrm{R}_{ +} \). Substituting \(\hat{\lambda }_{i} = \lambda _{i}\) (\(i = 1,2\)) in (13), we still have

$$\begin{aligned} I =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}} f(x)\,dx \\ >&\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\hat{\lambda }_{1}, \hat{\lambda }_{2}) \\ &{}\times \biggl[ \int _{0}^{\infty } x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \hat{\lambda }_{2}) - 1}(n - \xi ){}^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(15)

By reverse Hölder’s inequality (cf. [31]), we still have

$$\begin{aligned} B(\hat{\lambda }_{1},\hat{\lambda }_{2}) =& k_{\lambda } \biggl(\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q} \biggr) \\ =& \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\frac{\lambda - \lambda _{2}}{p} + \frac{\lambda _{1}}{q} - 1} \,du = \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} \bigl( u^{\frac{\lambda - \lambda _{2} - 1}{p}} \bigr) \bigl(u^{\frac{\lambda _{1} - 1}{q}} \bigr)\,du \\ \ge& \biggl[ \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\lambda - \lambda _{2} - 1} \,du \biggr]^{\frac{1}{p}} \biggl[ \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\lambda _{1} - 1} \,du \biggr]^{\frac{1}{q}} \\ =& \biggl[ \int _{0}^{\infty } \frac{1}{(1 + v)^{\lambda }} v^{\lambda _{2} - 1} \,dv \biggr]^{\frac{1}{p}} \biggl[ \int _{0}^{\infty } \frac{1}{(1 + u)^{\lambda }} u^{\lambda _{1} - 1} \,du \biggr]^{\frac{1}{q}} \\ &{}= \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}}. \end{aligned}$$
(16)

In view of \(\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}(k_{\lambda } (\lambda _{2}))^{\frac{1}{p}}(k_{\lambda } (\lambda _{1}))^{\frac{1}{q}}\) being the best possible constant factor in (12), by (15), we have the following inequality:

$$ \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}}\ge \frac{\Gamma (\lambda )}{\alpha ^{1.p}\Gamma (\lambda + m)}B(\hat{\lambda }_{1},\hat{ \lambda }_{2}) ( \in \mathrm{R}_{ +} ), $$

namely, \(B(\hat{\lambda }_{1},\hat{\lambda }_{2}) \le (k_{\lambda } (\lambda _{2}))^{\frac{1}{p}}(k_{\lambda } (\lambda _{1}))^{\frac{1}{q}}\), and then (16) keeps the form of equality.

We observe that (16) keeps the form of equality if and only if there exist constants A and B (cf. [31]) such that they are not both zero and \(Au^{\lambda - \lambda _{2}} = Bu^{\lambda _{1}}\) a.e. in \(\mathrm{R}_{ +} \). Assuming that \(A \ne 0\), we find \(u^{\lambda - \lambda _{2} - \lambda _{1}} = \frac{B}{A}\) a.e. in \(\mathrm{R}_{ +} \), namely, \(\lambda - \lambda _{2} - \lambda _{1} = 0\). Hence we have \(\lambda _{1} + \lambda _{2} = \lambda \).

The theorem is proved. □

Equivalent forms and some particular inequalities

Theorem 3

For \(p < 0\) (\(0 < q < 1\)) , we have the following reverse half-discrete Mulholland-type inequality equivalent to (12):

$$\begin{aligned} J : =& \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{p\alpha \hat{\lambda }_{2} - 1}(n - \xi )^{ - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\ >& \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \biggl[ \int _{0}^{\infty } x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}}. \end{aligned}$$
(17)

In particular, for \(\lambda _{1} + \lambda _{2} = \lambda \), we have the following inequality equivalent to (13):

$$\begin{aligned}& \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{p\alpha \lambda _{2} - 1}(n - \xi )^{ - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} B(\lambda _{1},\lambda _{2}) \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}}. \end{aligned}$$
(18)

Proof

Suppose that (17) is valid. By reverse Hölder’s inequality, we have

$$\begin{aligned} I =& \sum_{n = 2}^{\infty } \biggl\{ \bigl[\ln (n - \xi ) \bigr]^{\alpha \hat{\lambda }_{2} - \frac{1}{p}} (n - \xi )^{ - \frac{1}{p}} \int _{0}^{\infty } \frac{f(x)\,dx}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}} \biggr\} \\ &{}\times \bigl\{ \bigl[\ln (n - \xi ) \bigr]^{ - \alpha \hat{\lambda }_{2} + \frac{1}{p}}(n - \xi )^{\frac{1}{p}}a_{n} \bigr\} \\ \ge& J \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \hat{\lambda }_{2}) - 1} (n - \xi )^{q - 1}a_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(19)

Then, by (17), we have (12).

On the other hand, assuming that (12) is valid, we set

$$ a_{n}: = \bigl[\ln (n - \xi ) \bigr]^{p\alpha \lambda _{2} - 1}(n - \xi )^{ - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \biggr]^{p - 1},\quad n \in \mathrm{N}\backslash \{ 1\}. $$

If \(J = \infty \), then (17) is naturally valid; if \(J = 0\), then it is impossible that makes (17) valid, i. e., \(J > 0\). Suppose that \(0 < J < \infty \). By (12), we have

$$\begin{aligned}& \infty > \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \hat{\lambda }_{2}) - 1} (n - \xi )^{q - 1}a_{n}^{q} = J^{p} = I \\& \hphantom{\infty}> \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \biggl[ \int _{0}^{\infty } x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)\,dx \biggr]^{\frac{1}{p}} J^{p - 1} > 0, \\& J = \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \hat{\lambda }_{2}) - 1} (n - \xi )^{q - 1}a_{n}^{q} \Biggr\} ^{\frac{1}{p}} \\& \hphantom{J}> \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \biggl[ \int _{0}^{\infty } x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)\,dx \biggr]^{\frac{1}{p}}, \end{aligned}$$

namely, (17) follows, which is equivalent to (12).

The theorem is proved. □

Theorem 4

For \(p < 0\) (\(0 < q < 1\)) , if \(\lambda _{1} + \lambda _{2} = \lambda \), then the constant factor

$$ \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} $$

in (17) is best possible. On the other hand, if we add the condition that \(\lambda - \lambda _{1} \le \frac{1}{\alpha } \), the same constant factor in (17) is best possible, then we have \(\lambda _{1} + \lambda _{2} = \lambda \).

Proof

If \(\lambda _{1} + \lambda _{2} = \lambda \), then by Theorem 2, the constant factor

$$ \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} $$

in (12) is best possible. By (19), the constant factor in (17) is still best possible. Otherwise, we would reach a contradiction that the constant factor in (12) is not best possible.

On the other hand, if the constant factor in (17) is best possible, then, by the equivalency of (17) and (12), in view of \(J^{p} = I\) (see the proof of Theorem 3), we still can show that the constant factor in (12) is best possible. By the assumption and Theorem 2, we have \(\lambda _{1} + \lambda _{2} = \lambda \).

The theorem is proved. □

Remark 1

(i) For \(\alpha = 1\) in (13) and (18), we have the following equivalent inequalities:

$$\begin{aligned}& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{\ln ^{\lambda + m}e^{x}(n - \xi )} f(x)\,dx \\& \quad >\frac{\Gamma (\lambda )}{\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}) \\& \qquad {}\times \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \lambda _{2}) - 1}(n - \xi ){}^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}, \end{aligned}$$
(20)
$$\begin{aligned}& \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{p\lambda _{2} - 1}(n - \xi )^{ - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{\ln ^{\lambda + m}e^{x}(n - \xi )}\,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > \frac{\Gamma (\lambda )}{\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}) \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}}. \end{aligned}$$
(21)

(ii) For \(\xi = 0\) in (13) and (18), we have the following equivalent inequalities:

$$\begin{aligned}& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{(x + \ln ^{\alpha } n)^{\lambda + m}} f(x)\,dx \\& \quad >\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}) \\& \qquad {}\times \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \Biggl[ \sum_{n = 2}^{\infty } (\ln n)^{q(1 - \alpha \lambda _{2}) - 1}n{}^{q - 1} a_{n}^{q} \Biggr]^{\frac{1}{q}}, \end{aligned}$$
(22)
$$\begin{aligned}& \Biggl\{ \sum_{n = 2}^{\infty } \frac{(\ln n)^{p\alpha \lambda _{2} - 1}}{n} \biggl[ \int _{0}^{\infty } \frac{f(x)}{(x + \ln ^{\alpha } n)^{\lambda + m}}\,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}) \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}}. \end{aligned}$$
(23)

Hence,(13) (resp. (18)) is a more accurate form of (22) (resp. (23)).

(ii) For \(\xi = \frac{1}{2}\) in (13) and (18), we have the following equivalent inequalities:

$$\begin{aligned}& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \frac{1}{2})]^{\lambda + m}} f(x)\,dx \\& \quad >\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}) \\& \qquad {}\times \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \\& \qquad {}\times \Biggl\{ \sum_{n = 2}^{\infty } \biggl[\ln \biggl(n - \frac{1}{2} \biggr) \biggr]^{q(1 - \alpha \lambda _{2}) - 1} \biggl(n - \frac{1}{2} \biggr){}^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}, \end{aligned}$$
(24)
$$\begin{aligned}& \Biggl\{ \sum_{n = 2}^{\infty } \biggl[\ln \biggl(n - \frac{1}{2} \biggr) \biggr]^{p\alpha \lambda _{2} - 1} \biggl(n - \frac{1}{2} \biggr)^{ - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{[x + \ln ^{\alpha } (n - \frac{1}{2})]^{\lambda + m}}\,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}) \biggl[ \int _{0}^{\infty } x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}}. \end{aligned}$$
(25)

The constant factors in the above inequalities are all best possible.

Another kind of reverses

Similar to Lemma 2, we have the following.

Lemma 4

For \(0 < p < 1\) (\(q < 0\)), we have the following reverse Mulholland-type inequality:

$$\begin{aligned} I_{0} =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda }} f^{(m)}(x)\,dx > \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \\ &{}\times \biggl\{ \int _{0}^{\infty } \biggl[1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr]x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr\} ^{\frac{1}{p}} \\ &{}\times \Biggl\{ \sum_{n = 2}^{\infty } \bigl[ \ln (n - \xi ) \bigr]^{q(1 - \alpha \hat{\lambda }_{2}) - 1}(n - \xi )^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(26)

Theorem 5

For \(0 < p < 1\) (\(q < 0\)), we have the following equivalent reverse inequalities:

$$\begin{aligned}& I = \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}} f(x)\,dx > \frac{\Gamma (\lambda )}{\Gamma (\lambda + m)} \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \\& \hphantom{I=}{}\times \biggl[ \int _{0}^{\infty } \biggl(1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr)x^{p(1 - \stackrel{\leftarrow }{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \\& \hphantom{I=}{}\times \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \stackrel{\leftarrow }{\lambda }_{2}) - 1}(n - \xi )^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}, \end{aligned}$$
(27)
$$\begin{aligned}& J = \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{p\alpha \hat{\lambda }_{2} - 1}(n - \xi )^{ - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \hphantom{J}> \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} \bigl(k_{\lambda } (\lambda _{2}) \bigr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} \\& \hphantom{J>}{}\times \biggl[ \int _{0}^{\infty } \biggl(1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr)x^{p(1 - \hat{\lambda }_{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}}. \end{aligned}$$
(28)

In particular, for \(\lambda _{1} + \lambda _{2} = \lambda \), we have the following equivalent reverse inequalities:

$$\begin{aligned}& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{a_{n}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}} f(x)\,dx \\& \quad > \frac{\Gamma (\lambda )}{\alpha ^{1p}\Gamma (\lambda + m)} B(\lambda _{1},\lambda _{2}) \\& \qquad {}\times \biggl[ \int _{0}^{\infty } \biggl(1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr)x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}} \\& \qquad {}\times \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2}) - 1}(n - \xi )^{q - 1} a_{n}^{q} \Biggr\} ^{\frac{1}{q}}, \end{aligned}$$
(29)
$$\begin{aligned}& \Biggl\{ \sum_{n = 2}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{p\alpha \lambda _{2} - 1}(n - \xi )^{ - 1} \biggl[ \int _{0}^{\infty } \frac{f(x)}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \biggr]^{p} \Biggr\} ^{\frac{1}{p}} \\& \quad > \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)} B(\lambda _{1},\lambda _{2}) \biggl[ \int _{0}^{\infty } \biggl(1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr)x^{p(1 - \lambda _{1}) - 1} \bigl(f^{(m)}(x) \bigr)^{p}\,dx \biggr]^{\frac{1}{p}}, \end{aligned}$$
(30)

where the constant factor \(\frac{\Gamma (\lambda )}{\alpha ^{1p}\Gamma (\lambda + m)} B(\lambda _{1},\lambda _{2})\) is best possible.

Proof

We only prove that the constant factor in (29) is best possible. The others are omitted.

For any \(0 < \varepsilon < p\lambda _{1}\), we set

$$\begin{aligned}& \tilde{f}^{(0)}(x) = \tilde{f}(x): = \textstyle\begin{cases} 0,&0 < x < 1, \\ x^{\lambda _{1} + m - \frac{\varepsilon }{p} - 1},&x \ge 1 \end{cases}\displaystyle , \\& \tilde{a}_{n}: = \bigl[\ln (n - \xi ) \bigr]^{\alpha (\lambda _{2} - \frac{\varepsilon }{q}) - 1}(n - \xi )^{ - 1}\quad \bigl(n \in \mathrm{N}\backslash \{ 1\} \bigr), \end{aligned}$$

and find

$$ \tilde{f}^{(k)}(x) = \textstyle\begin{cases} 0,\quad 0 < x < 1, \\ \prod_{i = 0}^{k - 1} (\lambda _{1} + i - \frac{\varepsilon }{p})x^{\lambda _{1} + m - k - \frac{\varepsilon }{p} - 1},\quad x > 1 \end{cases}\displaystyle (k = 0, \ldots ,m) $$

satisfying \(\tilde{f}^{(k)}(0 + ) = 0\), \(\tilde{f}^{(k)}(x) = o(e{}^{tx})\) (\(t > 0\), \(x \to \infty \); \(k = 0, \ldots ,m - 1\)).

If there exists a constant \(M( \ge \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2}))\) such that (29) is valid when we replace \(\frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2})\) with M, then in particular we have

$$\begin{aligned} \tilde{I} =& \int _{0}^{\infty } \sum_{n = 2}^{\infty } \frac{\tilde{a}_{n}\tilde{f}(x)}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \\ >& M \biggl\{ \int _{0}^{\infty } \biggl(1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr)x^{p(1 - \lambda _{1}) - 1} \bigl(\tilde{f}^{(m)}(x) \bigr)^{p}\,dx \biggr\} ^{\frac{1}{p}}. \\ &{}\times \Biggl\{ \sum_{n = 2}^{\infty } \bigl[ \ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2}) - 1}(n - \xi )^{q - 1} \tilde{a}_{n}^{q} \Biggr\} ^{\frac{1}{q}}. \end{aligned}$$
(31)

By the decreasingness property of series, we find

$$\begin{aligned} \tilde{I} >& M\prod_{i = 0}^{m - 1} \biggl( \lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl[ \int _{1}^{\infty } \biggl(1 - O \biggl( \frac{1}{x^{\lambda _{2}}} \biggr) \biggr)x^{p(1 - \lambda _{1}) - 1} x^{p(\lambda _{1} - 1) - \varepsilon }\,dx \biggr]^{\frac{1}{p}} \\ &{}\times \Biggl\{ \sum_{n = 2}^{\infty } \bigl[ \ln (n - \xi ) \bigr]^{q(1 - \alpha \lambda _{2}) - 1}(n - \xi )^{q - 1} \bigl[\ln (n - \xi ) \bigr]^{q\alpha \lambda _{2} - \alpha \varepsilon - q}(n - \xi )^{ - q} \Biggr\} ^{\frac{1}{q}} \\ =& M\prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl[ \int _{1}^{\infty } x^{ - \varepsilon - 1}\,dx - \int _{1}^{\infty } O \biggl(\frac{1}{x^{\lambda _{2} + \varepsilon + 1}} \biggr) \,dx \biggr]^{\frac{1}{p}} \\ &{}\times \Biggl\{ \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \sum_{n = 3}^{\infty } \bigl[\ln (n - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(n - \xi )^{ - 1} \Biggr\} ^{\frac{1}{q}} \\ >& M\prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \biggl(\frac{1}{\varepsilon } - O(1) \biggr)^{\frac{1}{p}} \\ &{}\times \biggl\{ \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \int _{2}^{\infty } \bigl[\ln (y - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(y - \xi )^{ - 1}\,dy \biggr\} ^{\frac{1}{q}} \\ =& \frac{M}{\varepsilon } \prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \bigl(1 - \varepsilon O(1) \bigr)^{\frac{1}{p}} \\ &{}\times \biggl\{ \varepsilon \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \frac{1}{\alpha } \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon } \biggr\} ^{\frac{1}{q}}. \end{aligned}$$

Replacing λ with \(\lambda + m\), setting \(\tilde{\lambda }_{2}: = \lambda _{2} + \frac{\varepsilon }{p} \in (0,\lambda + m)\), \(\tilde{\lambda }_{1}: = \lambda _{1} + m - \frac{\varepsilon }{p} \in (0,\lambda + m)\) in (9), we have

$$\begin{aligned} \tilde{I} =& \sum_{n = 2}^{\infty } \biggl\{ \bigl[\ln (n - \xi ) \bigr]^{\alpha (\lambda _{2} + \frac{\varepsilon }{p})} \int _{1}^{\infty } \frac{x^{\lambda _{1} + m - \frac{\varepsilon }{p} - 1}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \biggr\} \bigl[\ln (n - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(n - \xi )^{ - 1} \\ \le& \sum_{n = 2}^{\infty } \biggl\{ \bigl[\ln (n - \xi ) \bigr]^{\alpha \tilde{\lambda }_{2}} \int _{0}^{\infty } \frac{x^{\tilde{\lambda }_{1} - 1}}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\,dx \biggr\} \bigl[\ln (n - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(n - \xi )^{ - 1} \\ =& \sum_{n = 2}^{\infty } \omega _{\lambda + m}( \tilde{\lambda }_{1},n) \bigl[\ln (n - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(n - \xi )^{ - 1} \\ =& k_{\lambda + m}(\tilde{\lambda }_{1}) \Biggl\{ \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \sum _{n = 3}^{\infty } \bigl[ \ln (n - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(n - \xi )^{ - 1} \Biggr\} \\ < & k_{\lambda + m}(\tilde{\lambda }_{1}) \biggl\{ \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \int _{2}^{\infty } \bigl[\ln (y - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(y - \xi )^{ - 1}\,dy \biggr\} \\ =& \frac{1}{\varepsilon \alpha } k_{\lambda + m}(\tilde{\lambda }_{1}) \bigl\{ \varepsilon \alpha \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon } \bigr\} . \end{aligned}$$

Based on the above results, we have

$$\begin{aligned}& \frac{1}{\alpha } k_{\lambda + m} \biggl(\lambda _{1} + m - \frac{\varepsilon }{p} \biggr) \bigl\{ \varepsilon \alpha \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon } \bigr\} \\& \quad > \varepsilon \tilde{I} \\& \quad > M\prod_{i = 0}^{m - 1} \biggl(\lambda _{1} + i - \frac{\varepsilon }{p} \biggr) \bigl(1 - \varepsilon O(1) \bigr)^{\frac{1}{p}} \biggl\{ \varepsilon \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon - 1}(2 - \xi )^{ - 1} + \frac{1}{\alpha } \bigl[\ln (2 - \xi ) \bigr]^{ - \alpha \varepsilon } \biggr\} ^{\frac{1}{q}}. \end{aligned}$$

For \(\varepsilon \to 0^{ +} \), in view of the continuity of the beta function, it follows that

$$ \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda {}_{1},\lambda _{2}) = \frac{\Gamma (\lambda {}_{1})\Gamma (\lambda {}_{2})}{\alpha ^{1/p}\Gamma (\lambda + m)} = \frac{B(\lambda _{1} + m,\lambda _{2})}{\alpha ^{1/p}\prod_{i = 0}^{m - 1} (\lambda _{1} + i)} \ge M. $$

Hence, \(M = \frac{\Gamma (\lambda )}{\alpha ^{1/p}\Gamma (\lambda + m)}B(\lambda _{1},\lambda _{2})\) is the best possible constant factor in (29).

The theorem is proved. □

In the same way of proving Theorem 4, we have the following.

Theorem 6

For \(0 < p < 1\) (\(q < 0\)), if we add the condition that \(\lambda - \lambda _{1} \le \frac{1}{\alpha }\), the constant factor

$$ \frac{\Gamma (\lambda )}{\Gamma (\lambda + m)} \biggl(\frac{1}{\alpha } k_{\lambda } (\lambda _{2}) \biggr)^{\frac{1}{p}} \bigl(k_{\lambda } (\lambda _{1}) \bigr)^{\frac{1}{q}} $$

in (27) (or (28)) is the best possible, then we have \(\lambda _{1} + \lambda _{2} = \lambda \).

Conclusions

In this paper, following the way of [4, 21], by means of the weight functions, Hermite–Hadamard’s inequality, and the techniques of real analysis, a new more accurate reverse half-discrete Mulholland-type inequality with the kernel as \(\frac{1}{[x + \ln ^{\alpha } (n - \xi )]^{\lambda + m}}\) involving one higher-order derivative function is given (for \(p < 0\), \(0 < q < 1\)) in Theorem 1. The equivalent statements of the best possible constant factor related to a few parameters, the equivalent forms, and several particular inequalities are provided in Theorems 24 and Remark 1. Another kind of the reverses is also considered (for \(0 < p < 1\), \(q < 0\)) in Theorems 56. The lemmas and theorems provide an extensive account of this type of inequalities.

Availability of data and materials

The data used to support the findings of this study are included within the article.

References

  1. 1.

    Hardy, G.H., Littlewood, J.E., Polya, G.: Inequalities. Cambridge University Press, Cambridge (1934)

    MATH  Google Scholar 

  2. 2.

    Krnić, M., Pečarić, J.: Extension of Hilbert’s inequality. J. Math. Anal. Appl. 324(1), 150–160 (2006)

    MathSciNet  Article  Google Scholar 

  3. 3.

    Yang, B.C.: On a generalization of Hilbert double series theorem. J. Nanjing Univ. Math. Biq. 18(1), 145–152 (2001)

    MathSciNet  MATH  Google Scholar 

  4. 4.

    Adiyasuren, V., Batbold, T., Azar, L.E.: A new discrete Hilbert-type inequality involving partial sums. J. Inequal. Appl. 2019, 127 (2019)

    MathSciNet  Article  Google Scholar 

  5. 5.

    Yang, B.C.: The Norm of Operator and Hilbert-Type Inequalities. Science Press, Beijing (2009)

    Google Scholar 

  6. 6.

    Krnić, M., Pečarić, J.: General Hilbert’s and Hardy’s inequalities. Math. Inequal. Appl. 8(1), 29–51 (2005)

    MathSciNet  MATH  Google Scholar 

  7. 7.

    Perić, I., Vuković, P.: Multiple Hilbert’s type inequalities with a homogeneous kernel. Banach J. Math. Anal. 5(2), 33–43 (2011)

    MathSciNet  Article  Google Scholar 

  8. 8.

    Huang, Q.L.: A new extension of Hardy–Hilbert-type inequality. J. Inequal. Appl. 2015, 397 (2015)

    MathSciNet  Article  Google Scholar 

  9. 9.

    He, B.: A multiple Hilbert-type discrete inequality with a new kernel and best possible constant factor. J. Math. Anal. Appl. 431, 889–902 (2015)

    MathSciNet  Article  Google Scholar 

  10. 10.

    Xu, J.S.: Hardy–Hilbert’s inequalities with two parameters. Adv. Math. 36(2), 63–76 (2007)

    MathSciNet  Google Scholar 

  11. 11.

    Xie, Z.T., Zeng, Z., Sun, Y.F.: A new Hilbert-type inequality with the homogeneous kernel of degree −2. Adv. Appl. Math. Sci. 12(7), 391–401 (2013)

    MathSciNet  MATH  Google Scholar 

  12. 12.

    Zheng, Z., Gandhi, R.R., Xie, Z.T.: A new Hilbert-type inequality with the homogeneous kernel of degree −2 and with the integral. Bull. Math. Sci. Appl. 3(1), 11–20 (2014)

    Google Scholar 

  13. 13.

    Xin, D.M.: A Hilbert-type integral inequality with the homogeneous kernel of zero degree. Math. Theory Appl. 30(2), 70–74 (2010)

    MathSciNet  Google Scholar 

  14. 14.

    Azar, L.E.: The connection between Hilbert and Hardy inequalities. J. Inequal. Appl. 2013, 452 (2013)

    MathSciNet  Article  Google Scholar 

  15. 15.

    Adiyasuren, V., Batbold, T., Krnić, M.: Hilbert-type inequalities involving differential operators, the best constants and applications. Math. Inequal. Appl. 18, 111–124 (2015)

    MathSciNet  MATH  Google Scholar 

  16. 16.

    Rassias, M.T., Yang, B.C.: On half-discrete Hilbert’s inequality. Appl. Math. Comput. 220, 75–93 (2013)

    MathSciNet  MATH  Google Scholar 

  17. 17.

    Yang, B.C., Krnić, M.: A half-discrete Hilbert-type inequality with a general homogeneous kernel of degree 0. J. Math. Inequal. 6(3), 401–417 (2012)

    MathSciNet  MATH  Google Scholar 

  18. 18.

    Rassias, M.T., Yang, B.C.: A multidimensional half-discrete Hilbert-type inequality and the Riemann zeta function. Appl. Math. Comput. 225, 263–277 (2013)

    MathSciNet  MATH  Google Scholar 

  19. 19.

    Rassias, M.T., Yang, B.C.: On a multidimensional half-discrete Hilbert-type inequality related to the hyperbolic cotangent function. Appl. Math. Comput. 242, 800–813 (2013)

    MathSciNet  MATH  Google Scholar 

  20. 20.

    Yang, B.C., Debnath, L.: Half-Discrete Hilbert-Type Inequalities. World Scientific, Singapore (2014)

    Book  Google Scholar 

  21. 21.

    Hong, Y., Wen, Y.M.: A necessary and sufficient condition of that Hilbert type series inequality with homogeneous kernel has the best constant factor. Ann. Math. 37A(3), 329–336 (2016)

    MathSciNet  MATH  Google Scholar 

  22. 22.

    Hong, Y.: On the structure character of Hilbert’s type integral inequality with homogeneous kernel and application. J. Jilin Univ. Sci. Ed. 55(2), 189–194 (2017)

    Google Scholar 

  23. 23.

    Hong, Y., Huang, Q.L., Yang, B.C., Liao, J.Q.: The necessary and sufficient conditions for the existence of a kind of Hilbert-type multiple integral inequality with the non-homogeneous kernel and its applications. J. Inequal. Appl. 2017, 316 (2017)

    MathSciNet  Article  Google Scholar 

  24. 24.

    Xin, D.M., Yang, B.C., Wang, A.Z.: Equivalent property of a Hilbert-type integral inequality related to the beta function in the whole plane. J. Funct. Spaces 2018, Article ID 2691816 (2018)

    MathSciNet  MATH  Google Scholar 

  25. 25.

    Hong, Y., He, B., Yang, B.C.: Necessary and sufficient conditions for the validity of Hilbert type integral inequalities with a class of quasi-homogeneous kernels and its application in operator theory. J. Math. Inequal. 12(3), 777–788 (2018)

    MathSciNet  Article  Google Scholar 

  26. 26.

    Huang, Z.X., Yang, B.C.: Equivalent property of a half-discrete Hilbert’s inequality with parameters. J. Inequal. Appl. 2018, 333 (2018)

    MathSciNet  Article  Google Scholar 

  27. 27.

    Yang, B.C., Wu, S.H., Wang, A.Z.: On a reverse half-discrete Hardy-Hilbert’s inequality with parameters. Mathematics 7, 1054 (2019)

    Article  Google Scholar 

  28. 28.

    Wang, A.Z., Yang, B.C., Chen, Q.: Equivalent properties of a reverse’s half-discrete Hilbert’s inequality. J. Inequal. Appl. 2019, 279 (2019)

    MathSciNet  Article  Google Scholar 

  29. 29.

    Yang, B.C., Wu, S.H., Liao, J.Q.: On a new extended Hardy-Hilbert’s inequality with parameters. Mathematics 8, 73 (2020). https://doi.org/10.3390/math8010073

    Article  Google Scholar 

  30. 30.

    Yang, B.C., Wu, S.H., Wang, A.Z.: On a reverse half-discrete Hardy-Hilbert’s inequality with parameters. Mathematics 7(11), 1054 (2019)

    Article  Google Scholar 

  31. 31.

    Kuang, J.C.: Applied Inequalities. Shangdong Science & Technology Press, Jinan (2004)

    Google Scholar 

  32. 32.

    Kuang, J.C.: Real and Functional Analysis (Continuation), vol. 2. Higher Education Press, Beijing (2015)

    Google Scholar 

Download references

Acknowledgements

The authors thank the referee for his useful proposal to reform the paper.

Funding

This work is supported by the National Natural Science Foundation of China (No. 61772140) and the Characteristic Innovation Project of Guangdong Provincial Colleges and Universities in 2020 (No. 2020KTSCX088). We are grateful for this help.

Author information

Affiliations

Authors

Contributions

BY carried out the mathematical studies, participated in the sequence alignment, and drafted the manuscript. QC participated in the design of the study and performed the numerical analysis. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Qiang Chen.

Ethics declarations

Competing interests

The authors declare that they have no competing interests.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Chen, Q., Yang, B. On two kinds of the reverse half-discrete Mulholland-type inequalities involving higher-order derivative function. J Inequal Appl 2021, 138 (2021). https://doi.org/10.1186/s13660-021-02674-z

Download citation

MSC

  • 26D15
  • 26D10
  • 26A42

Keywords

  • Weight function
  • Hermite–Hadamard’s inequality
  • Half-discrete Mulholland-type inequality
  • Higher-order derivative function
  • Parameter
  • Best possible constant factor